If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x * x) + -5 = 23 Multiply x * x (x2) + -5 = 23 x2 + -5 = 23 Reorder the terms: -5 + x2 = 23 Solving -5 + x2 = 23 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + x2 = 23 + 5 Combine like terms: -5 + 5 = 0 0 + x2 = 23 + 5 x2 = 23 + 5 Combine like terms: 23 + 5 = 28 x2 = 28 Simplifying x2 = 28 Take the square root of each side: x = {-5.291502622, 5.291502622}
| 8=2xb^2 | | -4+3x-1=4x+1 | | sin(19x)+sin(7x)=0 | | 64m=cm | | -16n+19=-15n-13 | | c=36(n+16) | | (5x+6y)(5x-6y)=0 | | 8=2(x-2) | | 45=9f | | 5x+6x=-11 | | X^3-3x^2-9x+3=0 | | (4x-5)(3-2x)=12-9(2x-5) | | 9+2+4=183652 | | 3(5x+6x)=108 | | 4x-72=-36 | | 4(x-14)=160 | | 4t+20-15= | | y=-4x^2+2x-3 | | 0=x^2+20x+208 | | 0=x^2+20+208 | | 40=2x+5+2x-3 | | tanx=0.5714 | | 3x+5(6.5)=37 | | 7(5y-4)=21y | | er^10=2er^1 | | x+3+2(x-4)=28 | | 14n^2+14n=0 | | 0.25x+3.5=20 | | 2k+6=11 | | 0.25x+3.5=0 | | 3(-y+8)+5y=37 | | 3(3+5m)-12+(-3m)= |